Spiritual tourism: understanding youth knowledge and needs - Ali, Nur Hidayah; Md Sawari, Siti Salwa; Mohamad, Zaleha (2022)
Spiritual Tourism is a term that is widely misinterpreted. Many studies used the phrase Spiritual Tourism interchangeably with "pilgrimage" or "religious tourism" and were unable to distinguish between the two of them. Commonly, Spiritual Tourism is not the same as Spiritual Tourism. The theory of Spiritual Tourism is broader than religious tourism. This is because, Spiritual Tourism is related to the tourist’s motivations, such as in terms of spiritual enlightenment, health, knowledge, humanism, or satisfaction. This study investigates youth knowledge and needs for Spiritual Tourism in Malaysia. A total 63 of respondents among Malaysian youth have participated in the research. The data were analyzed using IBM Statistical Package for Social Science version 26 through descriptive analysis. As a result, the majority of the youth were acknowledgeable to engage in spiritual activities, and they are aware of which characteristics should be applied and practiced during traveling. In terms of needs in Spiritual Tourism, youth agree that the presence of God is the most fundamental thing in their lives. It is hoped that this study contributes to the development of the tourism industry and helps them create a tourism product based on the youth's preference for a new niche brand called Spiritual Tourism